The Relevance Between The Concept Of Green Economy And Maqashid Al-Shari’ah: An Alternative Strategy For Addressing The Challenges Of Pollution And Climate Change - Nurun AN- Nisa, Chafifah; Cahyani, Rahma (Journal of Islamic Economic and Business Studies, 2024)
The global environmental crisi, marked by increasing pollution and extreme climate change, poses a significant threat to the sustainability of human life and ecosystem worldwide, including in Indonesia. This study explores the integration of green economy priciples with the islamic concept of maqashid al-shariah to address these challenges. Utilizing a qualitative research method with a literature review approach, the study highligths that investing in clean technology and green infrastructure is cricial for reducing air pollution and mitigating climate change impacts. Key strategies include adopting renewable energy sources, enhancing energy efficiency, and implementing strict emission standard. The findings indicate that these measures can improve air quality, reduce congestion, and promote sustainable development. The study also emphasizes the improtance of preserving natural capital and fostering intergenerational equity, alignimg with the principles of maqashid al-shariah. To achieve these goals, collaborative efforts among government, private sector, and communities are essential. The study recomends further research on the practical implementation of green economy strategies in various aIndonesian regions, the socio-economic impacts of such transition, and the development of educational programs to raise public awareness about environmental sustaibability. This approach aims to supprot Indonesia’s journey towards sustainable and eco-friendly economic growth.